Changes in salinity impact nitrogen removal and carbon preservation in coastal wetlands sediment - Ziyan Wang; Benoit Thibodeau (Estuarine, Coastal and Shelf Science, 2026)

Urbanisation accelerates carbon cycling and greenhouse gas emissions along a river-ocean continuum in the humid subtropics - Ho Wen Lo; Henry Charles James Thomas; Nga Man Chung; Jiao Liu; Qianqian Yang; Benoit Thibodeau; Lishan Ran (Environmental Research, 2026)

Highly reworked subtropical mudflat still provides carbon sequestration due to high sedimentation rate - Man Zhao; Mandy Wing Kwan So; Christelle Not; Benoit Thibodeau; Juan Diego Gaitán-Espitia (Estuarine, Coastal and Shelf Science, 2026)

Until their last breath: Persistence of a key ecological function of tropical sea cucumbers under ocean warming - Cheryl Chu; Benoit Thibodeau; Bayden D. Russell (Environmental Research, 2026)

Transcriptional responses and nutrient cycling dynamics in sea anemone Exaiptasia pallida under thermal stress and nitrogen pollution - Yifei Yu; Wenyan Nong; Ho Wen Lo; Nga Man Chung; Ho Yin Yip; Apple Pui Yi Chui; Benoit Thibodeau; Jerome Ho Lam Hui (Marine Pollution Bulletin, 2026)

In vitro digestibility, peptide profile, and bioactivities of water lentil (duckweed) protein compared to commercial protein isolates - Tristan Muller; Hairati Aboubacar; Mélissa Tourret; Jacinthe Thibodeau; Benoit Cudennec; Rozenn Ravallec; Laurent Bazinet (Food Research International, 2026)

Seagrasses under stress: Independent negative effects of elevated temperature and light reduction at multiple levels of organization - Alissa V. Bass; Laura J. Falkenberg; Benoit Thibodeau (Limnology and Oceanography, 2025)
Seagrasses are important foundation species, which support coastal biodiversity and provide socioeconomic benefits. However, seagrasses are threatened by anthropogenic changes, including the elevated temperature associated with marine heatwaves (MHWs) and light limitation from eutrophication or increased sedimentation. In this experiment, we exposed the seagrass Halophila ovalis to 10‐d of elevated temperature, simulating a MHW, and three light intensities to examine the impacts on multiple levels of organization, that is, growth, productivity, nitrogen cycling, and leaf microbiome. We found that both the MHW temperature and decreased light independently negatively impacted seagrass growth of new leaves, with decreased light also reducing new leaf area and rhizome elongation rate, and the occurrence of MHW temperatures increasing the rate of leaf loss. Similarly, chlorophyll concentration was altered by both stressors independently, with a common response to reduced light (increased chlorophyll concentration) significantly lower under the MHW temperature. Nitrogen assimilation rate into the leaves also decreased under both MHW temperature and reduced light availability. The leaf microbiome shifted in response to the MHW temperature and lower light, with these conditions prompting relatively more anaerobic microbes but less oxidative stress‐tolerant bacteria, and less prokaryotes performing phototrophy and (oxygenic) photoautotrophy. In conclusion, we show elevated temperature representing a MHW and light limitation can drive decreased seagrass growth, chlorophyll concentration, and cause shifts in leaf microbial functional groups, although there was little interaction between stressors. It is therefore important that good water clarity and habitat health is maintained to reduce the susceptibility of seagrasses to extreme climatic events.

Seasonality and local nutrient loading drive changes in organic carbon in seagrass ecosystems in Hong Kong - Amrit Kumar Mishra; Katie M. Watson; Ho Tun Ng; Man Zhao; Chanaka Isuranga Premarathne Maha Ranvilage; Dwi Wai Shan Jaimie; Tse Cham Man; Christelle Not; Benoit Thibodeau; Juan C. Astudillo; Juan Diego Gaitán-Espitia (Estuarine, Coastal and Shelf Science, 2025)

Tidal currents and atmospheric inorganic nitrogen contribute to diurnal variation of dissolved nutrients and chlorophyll a concentrations in Mirs Bay, Hong Kong - Ho Wen Lo; Xu Yu; Hanzhe Chen; Wai Ching Chu; Nga Man Chung; Sze Wing Lau; Jinjian Li; Shumin Liang; Kezheng Liao; Henry Charles James Thomas; Ziyan Wang; Zijing Zhang; et al. (Regional Studies in Marine Science, 2025)

Testing the deep‐sea glacial disturbance hypothesis as a cause of low, present‐day Norwegian Sea diversity and resulting steep latitudinal diversity gradient, using fossil records - Anna B. Jöst; Huai‐Hsuan M. Huang; Yuanyuan Hong; Chih‐Lin Wei; Henning A. Bauch; Benoit Thibodeau; Thomas M. Cronin; Hisayo Okahashi; Moriaki Yasuhara (Global Ecology and Biogeography, 2024)
Aim Within the intensively‐studied, well‐documented latitudinal diversity gradient, the deep‐sea biodiversity of the present‐day Norwegian Sea stands out with its notably low diversity, constituting a steep latitudinal diversity gradient in the North Atlantic. The reason behind this has long been a topic of debate and speculation. Most prominently, it is explained by the deep‐sea glacial disturbance hypothesis, which states that harsh environmental glacial conditions negatively impacted Norwegian Sea diversities, which have not yet fully recovered. Our aim is to empirically test this hypothesis. Specific research questions are: (1) Has deep‐sea biodiversity been lower during glacials than during interglacials? ( 2) Was there any faunal shift at the Mid‐Brunhes Event (MBE) when the mode of glacial–interglacial climatic change was altered? Location Norwegian Sea, deep sea (1819–2800 m), coring sites MD992277, PS1243, and M23352. Time period 620.7–1.4 ka (Middle Pleistocene–Late Holocene). Taxa studied Ostracoda (Crustacea). Methods We empirically test the deep‐sea glacial disturbance hypothesis by investigating whether diversity in glacial periods is consistently lower than diversity in interglacial periods. Additionally, we apply comparative analyses to determine a potential faunal shift at the MBE, a Pleistocene event describing a fundamental shift in global climate. Results The deep Norwegian Sea diversity was not lower during glacial periods compared to interglacial periods. Holocene diversity was exceedingly lower than that of the last glacial period. Faunal composition changed substantially between pre‐ and post‐MBE. Main conclusions These results reject the glacial disturbance hypothesis, since the low glacial diversity is the important precondition here. The present‐day‐style deep Norwegian Sea ecosystem was established by the MBE, more specifically by MBE‐induced changes in global climate, which has led to more dynamic post‐MBE conditions. In a broader context, this implies that the MBE has played an important role in the establishment of the modern polar deep‐sea ecosystem and biodiversity in general.

Salinity, mineralogy, porosity, and hydrodynamics as drivers of carbon burial in urban mangroves from a megacity - Laetitia Allais; Benoit Thibodeau; Nicole S. Khan; Sean A. Crowe; Stefano Cannicci; Christelle Not (Science of The Total Environment, 2024)

Coral carbonate-bound isotopes reveal monsoonal influence on nitrogen sources in Southeastern China's Greater Bay Area from the mid-Holocene until the Anthropocene - Jonathan D. Cybulski; Nicolas N. Duprey; Benoit Thibodeau; Moriaki Yasuhara; Naomi Geeraert; Nicole Leonard; Hubert B. Vonhof; Alfredo Martínez-García; David M. Baker (Marine Pollution Bulletin, 2023)

Genome of elegance coral Catalaphyllia jardinei (Euphylliidae) - Yifei Yu; Wenyan Nong; Wai Lok So; Yichun Xie; Ho Yin Yip; Jasmine Haimovitz; Thomas Swale; David M. Baker; William G. Bendena; Ting Fung Chan; Apple P. Y. Chui; Kwok Fai Lau; et al. (Frontiers in Marine Science, 2022)
Coral reefs are under stress throughout the world. To better understand the molecular mechanisms underlying coral biology and their genomic evolution, here we sequenced the genome and transcriptomes of elegance coral Catalaphyllia jardinei (Euphylliidae). This monotypic genus stony coral is widespread but rare, being found across the Indo-West Pacific, from the northern Indian Ocean, Australia, Philippines, to the South China Sea. Due to its popularity among aquarium hobbyists, it is an overexploited species collected in large quantities from the wild for aquarium trade. The assembled genome is ~ 651.3 Mb in total length and of high physical contiguity with a scaffold N50 size of 28.9 Mb. The gene copy numbers of abiotic stress regulator (heat shock protein family genes) and neuropeptides (GLWamide, GRFamide, PRGamide and HIRamide) are similar to other sequenced anthozoans, and we have also identified the first set of sesquiterpenoid biosynthetic pathway genes in coral. Sequencing of small RNAs allows us to identify 35 microRNAs in C. jardinei and update the number of conserved microRNAs in cnidarians. This study established a foundation for further investigation into the roles of sesquiterpenoids and microRNAs in development of coral and understand their responses to climate change. Due to the easiness to culture C. jardinei in reef tanks and the established resources in this study, we propose this species be adopted as a new laboratory model in environmental and ecological experiments aiming to understand coral biology and responses to environmental stressors.

Cold Water in a Warm World: Investigating the Origin of the Nordic Seas' Unique Surface Properties During MIS 11 - John M. Doherty; Benoit Thibodeau (Frontiers in Marine Science, 2018)

Consistency in coral skeletal amino acid composition offshore of Palau in the western Pacific warm pool indicates no impact of decadal variability in nitricline depth on primary productivity - Branwen Williams; Benoit Thibodeau; Yoshito Chikaraishi; Naohiko Ohkouchi; Andrew Walnum; Andréa G. Grottoli; Patrick L. Colin (Limnology and Oceanography, 2017)
The depth of the thermocline and associated nitricline in the western Pacific warm pool (WPWP) vary over time in response to changes in larger ocean‐atmosphere climate patterns. A shoaling of the nitricline in the WPWP brings nitrate‐rich seawater ( > 4 μ mol kg −1 ) above the base of the euphotic zone, stimulating primary productivity. Here, we test if decadal variability in the nitricline depth is driving changes in regional primary productivity and source nitrate dynamics. We use the nitrogen isotopic composition (δ 15 N) of amino acids in the skeleton of a proteinaceous coral collected from the base of the euphotic zone in the WPWP. In proteinaceous corals, as in most organic life, the δ 15 N of phenylalanine matches that of the ambient nitrate while the δ 15 N of trophic amino acids reflect subsequent trophic transfer of the nitrogen prior to incorporation into the coral's food, suspended particulate organic matter. Consistency of the trophic position of the coral calculated from the δ 15 N composition of the coral skeletal amino acids over its 56 yr lifespan suggest that decadal variability in nitricline depth and subsequent shifts in nitrate availability to the euphotic zone have not impacted primary productivity offshore of Palau in the WPWP. This is important when considering the current external forcing of Pacific Ocean climate patterns and the resulting impacts on the global carbon cycle in the Palau region of the WPWP.

Aerobic respiration and hypoxia in the Lower St. Lawrence Estuary: Stable isotope ratios of dissolved oxygen constrain oxygen sink partitioning - Moritz F. Lehmann; Bruce Barnett; Y. Gélinas; Denis Gilbert; Roxane J. Maranger; Alfonso Mucci; Bjorn Sundby; Benoit Thibodeau (Limnology and Oceanography, 2009)
We measured the concentration and the stable isotope ratios of dissolved oxygen in the water column in the Estuary and Gulf of St. Lawrence to determine the relative importance of pelagic and benthic dissolved oxygen respiration to the development of hypoxic deep waters. The progressive landward decrease of dissolved oxygen in the bottom waters along the axis of the Laurentian Channel (LC) is accompanied by an increase in the 18 O: 16 O ratio, as would be expected from O‐isotope fractionation associated with bacterial oxygen respiration. The apparent O‐isotope effect, ε O‐app , of 10.8% reveals that community O‐isotope fractionation is significantly smaller than if bacterial respiration occurred solely in the water column. Our observation can best be explained by a contribution of benthic O 2 consumption occurring with a strongly reduced O‐isotope effect at the scale of sediment‐water exchange (ε O‐sed ~ 7%). The value for ε O‐sed was estimated from benthic O 2 exchange simulations using a one‐dimensional diffusion‐reaction O‐isotope model. Adopting this ε O‐sed value, and given the observed community O‐isotope fractionation, we calculate that approximately two thirds of the ecosystem respiration occurs within the sediment, in reasonable agreement with direct respiration measurements. Based on the difference between dissolved oxygen concentrations in the deep waters of the Lower St. Lawrence Estuary and in the water that enters the LC at Cabot Strait, we estimate an average respiration rate of 5500 mmol O 2 m −2 yr −1 for the 100‐m‐thick layer of bottom water along the LC, 3540 mmol O 2 m −2 yr −1 of which is attributed to bacterial benthic respiration.